1992
DOI: 10.1200/jco.1992.10.12.1933
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative systemic chemotherapy followed by adjuvant postoperative intraperitoneal therapy for gastric cancer: a University of Southern California pilot program.

Abstract: This novel approach to the treatment of adenocarcinoma of the stomach is feasible. The neoadjuvant systemic therapy results in significant primary tumor regression. The determination of whether systemic or IP components of the program contribute to decreased recurrence or increased survival awaits a prospectively randomized clinical trial.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
38
0
3

Year Published

1995
1995
2010
2010

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 103 publications
(43 citation statements)
references
References 24 publications
2
38
0
3
Order By: Relevance
“…This compares well with previous reports of histopathologic response in gastric carcinoma, in which complete regression rates ranged from 0% to 12%. 3,4,6,7,28,29 We found no cases with complete regression. This is also due in part to the finding that the tumor beds of the specimens were sectioned completely so that even small remnants of residual tumor could be found, a procedure that was not described in the studies of Kiyabu et al 16 or Yonemura et al 17 Regression corresponding to less than 10% residual tumor (Grade 1) was found in only 4 patients (11%).…”
Section: Discussionmentioning
confidence: 54%
See 2 more Smart Citations
“…This compares well with previous reports of histopathologic response in gastric carcinoma, in which complete regression rates ranged from 0% to 12%. 3,4,6,7,28,29 We found no cases with complete regression. This is also due in part to the finding that the tumor beds of the specimens were sectioned completely so that even small remnants of residual tumor could be found, a procedure that was not described in the studies of Kiyabu et al 16 or Yonemura et al 17 Regression corresponding to less than 10% residual tumor (Grade 1) was found in only 4 patients (11%).…”
Section: Discussionmentioning
confidence: 54%
“…This is a small percentage, particularly considering that clinical estimates of the proportion of patients with a good response are generally higher, with complete or major response rates ranging from 24% to 50%. 3,4,6,7,28,29 However, a true comparison between clinical and pathologic staging is not possible, because imaging techniques such as endoscopic ultrasound, spiral CT scan, and magnetic resonance imaging cannot adequately stage lymph nodes and because clinical staging is relatively imprecise. Therefore, statements about downstaging based on comparison of preoperative and postoperative UICC staging are inherently problematic.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…at 30 mg/kg over the first 7 days, followed by further administrations of 15 mg/kg over several additional days [18]. Similarly, high doses of FdUrd have been used more recently for therapy with bolus injections of 3 g daily (∌50 mg/kg) into the peritoneal cavity of patients with peritoneal tumor dissemination [28]. The difference between bolus injection and 24-h perfusion of FdUrd was studied by Sullivan et al [29].…”
Section: Discussionmentioning
confidence: 99%
“…Treatment regimens and results are detailed in Table 4. In two studies, intraperitoneal chemotherapy was added postoperatively to eligible patients (4,67,74). Inclusion criteria were not uniform and the preoperative staging used many different imaging techniques.…”
Section: Preoperative Chemotherapymentioning
confidence: 99%